(untitled) (Research, Society and Development, 2020)
It is known that assessment and management are present in school dynamics. Thus, this research aims to assess in the teachers’ conception the effects managed by the management of public schools in the state public network of Ceará, in the professional modality, located in the city of Fortaleza regarding the factors of planning, organization, direction and control. For this analysis, we considered the managerial nucleus and the teaching and administrative bodies (n = 31) in an attempt to understand the factors associated with the performance of students in the schools surveyed based on the planning, organization, direction and control cycle initially proposed by Deming (1986) and woven by Shewar (1920) and refined in contemporary times by Chiavenato (2014). The research methodology adopted was centered on Bruyne, Herman and Schoutheete’s (1977) quadripolar methodological strategy. The study is inserted in a qualitative approach, of a descriptive level and with basic purpose. It was concluded that it is a challenge to effectively experience the variation of the PDCA cycle in professional schools, given that it intends to change the conception of the school’s role, seeking a more democratic and participatory model.